The meandering narrative : poetry and illustration engage in a moment of indiscipline : demonstrated in an analysis of Sara Fanelli’s illuminated poem - And all men kill the thing they love - Kreuser, Carla Louise (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.